Perbandingan Efektivitas Dalam Pengelolaan Lembaga Pemasyarakatan (Lapas) Yang Mengalami Overcrowded di Negara Indonesia dan Brasil - Rizki Pratama, Muh Ersandi; Ansa, Ferdi; Irfandi, Fitra; Hafiidz Syam, Syahrul (UNES Law Review, 2024)
Indonesia is a country based on law. In addition to using the term rechtstaat, Indonesian literature also commonly uses another term, namely the rule of law, to mean "rule of law". This coaching system is implemented by Correctional Institutions or what is abbreviated as Lapas as regulated in Article 6 of Law Number 12 of 1995. Correctional Institutions must organize correctional institutions so that prisoners can be accepted back into society. The performance of a prison in implementing correctional services is greatly influenced by several factors, namely the quantity and quality of prison officers, adequate facilities and infrastructure, a coaching program that is tailored to interests and talents, and the existence of comparability. These factors complement each other. The method used in compiling this research is research with a normative juridical method approach, namely research that focuses on testing the application of rules or norms in law. The effectiveness of the management of overcrowded prisons in Indonesia and Brazil is very good. In Indonesia, which has made efforts to prevent overcrowding by using several alternative methods, such as a grand design for handling overcrowding in state detention centers and correctional institutions, there is institutional strengthening in correctional institutions. Brazil has made efforts to prevent overcrowding by privatizing correctional institutions and outsourcing.